THE EFFECT OF TASK-BASED LEARNING AND AUTHENTIC MATERIALS ON ENGLISH GRAMMATICAL LEARNING ACHIEVEMENT FOR STUDENTS IN A THAI HIGH SCHOOL - Asavajaruphan, Viroj; Sertpanya , Sarinrat; Ekwarangkoon, Pikun (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2025)
The objectives of this study aimed to compare the mean scores of students' English grammatical tests before and after receiving instruction using the task-based learning and authentic materials, and to investigate students' attitudes toward the learning approach. This study utilized a pre-experimental design (one-group pretest-posttest). The sample consisted of 50 eleventh-grade students from Marie Upatham School, chosen purposively from the first semester of the 2024 academic year. The instruments utilized in this study included: 1) a series of lesson plans spanning eight weeks, employing the task-based learning and authentic materials, 2) pre-post English grammatical tests, and 3) a questionnaire assessing students' perspectives on the task-based learning and authentic materials. The data were analyzed by paired sample t-test, mean, and standard deviation. The findings indicated a significant increase in students' English grammatical test scores after instruction using the task-based learning and authentic materials, with a level of significance of 0.05. Additionally, students showed positive attitudes toward the instructional method. These findings suggested the potential of the task-based learning and authentic materials to enhance English grammatical achievement, offering valuable insights for educators and researchers seeking to optimize teaching practices and educational outcomes.